FEATURES OF THE MACULAR AND PERIPAPILLARY CHOROID AND CHORIOCAPILLARIS IN EYES WITH NONEXUDATIVE AGE-RELATED MACULAR DEGENERATION. Issue 12 (December 2020) - Nam, Ki Tae; Chung, Hyun Woo; Jang, Sungmin; Kim, Seong-Woo; Oh, Jaeryung; Yun, Cheolmin
Abstract : Purpose: We investigated macular and peripapillary choroidal thickness (CT) and flow voids in the choriocapillaris in eyes with nonexudative age-related macular degeneration. Methods: We retrospectively reviewed the medical records of patients with nonexudative age-related macular degeneration and classified their eyes into three categories: pachydrusen, drusen, and subretinal drusenoid deposit. Mean macular and peripapillary CT and choriocapillaris flow void area were compared among the three groups. Results: The three groups included 29, 33, and 33 patients, respectively. The mean macular and peripapillary CT findings were 260.64 ± 75.85 µ m and 134.47 ± 46.28 µ m for the pachydrusen group; 163.63 ± 64.08 µ m and 93.47 ± 39.07 µ m for the drusen group; and 95.33 ± 28.87 µ m and 56.06 ± 11.64 µ m for the subretinal drusenoid deposit group (all, P < 0.001). Mean macular and peripapillary flow void area varied among the subretinal drusenoid deposit group (57.07 ± 6.16% and 55.38 ± 6.65%), drusen group (58.30 ± 6.98% and 49.11 ± 9.11%) and pachydrusen group (50.09 ± 5.77% and 45.47 ± 8.06%) (all P < 0.001). Conclusion: The peripapillary CT and flow voids in the choriocapillaris varied according to the features of drusen in nonexudative age-related macular degeneration eyes. Greater flow voids and thinner CT in eyes with subretinal drusenoid deposits may suggest that these eyes have diffuse choroidal abnormalities both in and outside the macula. Abstract : Supplemental Digital Content is Available in the Text.Peripapillary choroidal features were found to vary according to drusen type in eyes with non-neovascular age-related macular degeneration.